Anti-adhesion antibacterial lubricating wound dressing as well as preparation method and application thereof

By loading copper ions into gauze and wrapping them in polydimethylsiloxane, anti-adhesion and antibacterial wound dressings were prepared, which solved the pain problem when the bacterial shielding effect of traditional dressings was weakened and replaced after oozing, and achieved the Effective antibacterial and wound healing promotion for E. coli and Staphylococcus aureus.

CN119139528APending Publication Date: 2024-12-17ZHENGZHOU UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411289258.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

Traditional medical dressings are prone to weakening the bacterial shielding effect due to ooze during use, and may cause pain and secondary trauma when replaced. The preparation process of existing antibacterial materials is complicated and inconvenient for large-scale production.

Method used

An antibacterial lubricating wound dressing iPDMS/Cu-IG is prepared by soaking copper wire in NaOH solution to load copper ions onto a normal gauze and wrapping it in polydimethylsiloxane (PDMS) to prevent adhesion and possession Excellent lubricity and antibacterial properties.

Benefits of technology

The dressing exhibits excellent antibacterial properties in E. coli and Staphylococcus aureus, and is simple in preparation, low in production cost, suitable for large-scale production, and can effectively prevent wound contamination and promote healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119139528A_ABST
    Figure CN119139528A_ABST
Patent Text Reader

Abstract

The invention discloses an anti-adhesion antibacterial lubricating wound dressing as well as a preparation method and application thereof, and belongs to the technical field of preparation of biomedical materials. The preparation method comprises the following steps: soaking a copper wire in a 10 wt.% NaOH solution to obtain a Cu (II) solution, then soaking common gauze in the Cu (II) solution, enabling the gauze to load copper ions to finally obtain copper ion gauze Cu-IG, washing the Cu-IG with deionized water for multiple times until the pH value of the cleaned solution is neutral, and drying at room temperature for later use; and immersing the dried sample into a mixed solution of polydimethylsiloxane and n-hexane, curing, and immersing into dimethyl silicone oil again to finally obtain the iPDMS / Cu-IG. According to the iPDMS / Cu-IG lubricating gauze and the preparation method thereof, iPDMS / Cu-IG is prepared, the PDMS wrapping the outer layer of the gauze fiber endows the iPDMS / Cu-IG with wound adhesion prevention performance, the excellent lubricity of the iPDMS / Cu-IG ensures that a sample has good antifouling performance, and in addition, the existence of copper ions ensures that the iPDMS / Cu-IG lubricating gauze has excellent antibacterial performance on escherichia coli and staphylococcus aureus.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of biomedical materials, and in particular relates to an antibacterial lubricating wound dressing with anti-adhesion function, and a preparation method and application thereof. Background Art

[0002] Traditional medical dressings are the main dressings used in clinical wound care. They are low-cost and have the ability to protect wounds. They are the longest-used medical dressings. However, traditional medical dressings have limitations in use. For example, when the dressing is soaked with exudate or other liquids, the shielding effect on bacteria becomes weaker, resulting in an increased risk of wound infection; and after the gauze absorbs the exudate, it will stick tightly to the wound surface. When changing it, it will not only cause pain, but may also cause secondary trauma.

[0003] Since the introduction of penicillin, it has been believed that antibiotics will inhibit bacterial infections. However, antibiotic resistance reduces its antibacterial effectiveness, leading to many treatment failures in the clinic. Therefore, it is necessary to develop effective strategies to address antibiotic resistance. At present, inorganic metal antibacterial materials have non-specific bacterial toxicity mechanisms, which not only make it difficult for bacteria to develop resistance, but also expand the antibacterial spectrum. In addition, most metal nanoparticles have significant antibacterial effects on both Gram-positive and Gram-negative bacteria. In particular, copper ions are widely used in the biomedical field because of their excellent antibacterial properties, low cost and low toxicity.

[0004] At present, many researchers have focused on loading copper into various medical materials for use against bacteria in wounds. For example, in the literature, Ionic liquids enable the preparation of a copper-loaded gel with transdermal delivery function for wound dressings [J]. Biomaterials Science, 2022, 10, they mixed dopamine (DA) with polyvinyl alcohol (PVA) and copper ions, and then added ionic liquid (IL) choline-glycolate (CGLY) to the mixture to form an ionic gel. Among them, CGLY can promote the release of copper ions to kill drug-resistant bacteria, but the low permeability of the hydrogel may lead to insufficient oxygen supply in the wound, which has an adverse effect on the wound. For example, in the literature, Bacterialcellulose-based dressings with photothermal bactericidalactivity and pro-angiogenic ability for infected wound healing [J]. 2023, 160, a multifunctional dressing based on bacterial cellulose was developed, which is beneficial to the proliferation, migration and angiogenesis of endothelial cells in vitro through the released copper ions. However, there are problems such as complex preparation process and inconvenience of large-scale preparation.

[0005] The ideal wound dressing must not only protect the wound from external bacteria and environmental invasion, but also have good biocompatibility, and its preparation process must be simple and easy to prepare on a large scale. During the wound healing process, it can also promote the corresponding cells to secrete various growth factors to improve inflammation at the wound, promote the growth of granulation tissue at the wound, collagen deposition and angiogenesis.

[0006] Therefore, based on the above-mentioned problems and the vision of an ideal dressing, there is an urgent need to design a dressing that can prevent secondary injury, effectively block external contamination, have good antibacterial ability and promote wound healing. Summary of the invention

[0007] The purpose of the present invention is to solve the problems existing in the existing dressings, provide an antibacterial lubricating wound dressing with anti-adhesion, and a preparation method and application thereof, wherein the antibacterial lubricating wound dressing iPDMS / Cu-IG is prepared by immersing copper wire in NaOH so that copper ions are loaded onto ordinary gauze; wherein the PDMS wrapped in the outer layer of the gauze fiber gives the iPDMS / Cu-IG the performance of preventing adhesion of the wound, and its excellent lubricity ensures that the sample has good antifouling performance, and in addition, the presence of copper ions ensures that the iPDMS / Cu-IG lubricating gauze has excellent antibacterial properties against Escherichia coli and Staphylococcus aureus.

[0008] To achieve the above object, the present invention adopts the following technical solution: a method for preparing an antibacterial lubricating wound dressing with anti-adhesion properties, comprising the following steps: S1. Soak the copper wire in a 10 wt.% NaOH solution to obtain a Cu(Ⅱ) solution, and then immerse the ordinary gauze in the Cu(Ⅱ) solution. In an alkaline environment, the hydrogen bond network on the gauze is destroyed, causing the cellulose matrix to swell. Subsequently, the copper ions diffuse into the gaps between the cellulose crystals and coordinate with the oxygen atoms of the hydroxyl groups on the cellulose chain, so that the gauze is loaded with copper ions and finally obtains the copper ion gauze Cu-IG. S2, washing the copper ion gauze Cu-IG sample obtained above with deionized water for multiple times until the pH value of the washed solution is neutral, and drying at room temperature for standby use; S3. The dried copper ion gauze Cu-IG sample is immersed in a mixed solution of polydimethylsiloxane and n-hexane for solidification, and then immersed in dimethyl silicone oil again to finally obtain the antibacterial lubricating wound dressing iPDMS / Cu-IG.

[0009] In step S1, the time for the copper ion loading of ordinary gauze to reach stability is 15 minutes to 48 hours.

[0010] In the step S3, the ratio of polydimethylsiloxane to n-hexane (w / v) is 10% to 70%.

[0011] In the step S3, polydimethylsiloxane is formed by thermally polymerizing a PDMS matrix and a curing agent in a certain proportion, wherein the mass ratio (w / w) of the PDMS matrix and the curing agent is 20-80:1.

[0012] In step S3, the viscosity of the dimethyl silicone oil is 20 mPa•s or 200 mPa•s, and the immersion time in the dimethyl silicone oil is 40 min.

[0013] The invention also discloses an antibacterial lubricating wound dressing with anti-adhesion function prepared by the preparation method.

[0014] The invention also discloses application of the antibacterial lubricating wound dressing with anti-adhesion function in the antibacterial field of medical materials.

[0015] The beneficial effects of the present invention are: 1) The present invention prepares an antibacterial lubricating wound dressing iPDMS / Cu-IG by immersing copper wire in NaOH to load copper ions onto ordinary gauze; wherein the PDMS wrapped around the outer layer of the gauze fiber gives the iPDMS / Cu-IG the ability to prevent wound adhesion, and its excellent lubricity ensures that the sample has good antifouling properties. In addition, the presence of copper ions ensures that the iPDMS / Cu-IG lubricating gauze has excellent antibacterial properties against Escherichia coli and Staphylococcus aureus.

[0016] 2) The preparation method of iPDMS / Cu-IG of the present invention is simple, has low production cost, and is conducive to large-scale preparation and production. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a flow chart for preparing the antibacterial lubricating wound dressing iPDMS / Cu-IG of the present invention; Figure 2 X-ray photoelectron spectra of iPDMS / Cu-IG and ordinary gauze prepared in Example 6 of the present invention; Figure 3 is the copper content of the Cu-IG prepared in Examples 1 to 6 of the present invention at different immersion times; Figure 4 The scanning electron microscope images of Cu-IG treated with polydimethylsiloxane and n-hexane in different ratios (w / v) prepared in Examples 6 to 9 of the present invention are shown; Figure 5 Graphs showing the adhesion test results of sample gauze, vaseline gauze and ordinary gauze treated with PDMS and curing agent in different proportions prepared in Examples 6 and 10 to 15 of the present invention; Figure 6 The softness and hardness test results of the sample gauze and ordinary gauze treated with PDMS and curing agent in different proportions prepared in Examples 6 and 10 to 15 of the present invention are shown in FIG. Figure 7 The graph is a result of the adaptive determination of the gauze prepared in Example 6 and Example 16 of the present invention soaked in dimethyl silicone oils of different viscosities; Figure 8This is a statistical result diagram of fluorescence intensity on ordinary gauze (Ordinary gauze) and iPDMS / Cu-IG prepared in Example 6 when fluorescent bacteria are used in the present invention to simulate skin surface contamination; Fig. 9 This is a comparative study result of the moisturizing effects of ordinary gauze, vaseline gauze and iPDMS / Cu-IG prepared in Example 6 measured in the present invention; Fig.10 This is a comparative study result of the air permeability effects of ordinary gauze, vaseline gauze and iPDMS / Cu-IG prepared in Example 6 measured in the present invention; Fig.11 The antibacterial effect and colony count statistics of the ordinary gauze and the iPDMS / Cu-IG prepared in Example 6 after co-incubation with Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus) for 24 hours measured in the present invention; Fig.12 Cell activity diagrams of ordinary gauze, vaseline gauze, Atrauman® Ag, and iPDMS / Cu-IG prepared in Example 6 measured in the present invention; Fig.13 Schematic diagram of the wound healing process of SD rats with ordinary gauze, Atrauman® Ag, and iPDMS / Cu-IG prepared in Example 6 as measured in the present invention; Fig.14 Figure a shows the H&E staining results of wound tissues of ordinary gauze, Atrauman® Ag, and iPDMS / Cu-IG prepared in Example 6 on the 7th and 14th days of wound healing in SD rats and the statistical graph of granulation tissue thickness in Figure b; Fig.15 Figure a shows the Masson staining results of wound tissue of SD rats with ordinary gauze, Atrauman® Ag, and iPDMS / Cu-IG prepared in Example 6 at the 7th and 14th days of wound healing, and Figure b shows the statistical graph of collagen deposition rate. DETAILED DESCRIPTION

[0018] The present invention is further explained below in conjunction with the accompanying drawings and specific embodiments.

[0019] like Figure 1Shown is a flow chart of the preparation of iPDMS / Cu-IG of the present invention, according to which a sample dressing is produced.

[0020] Embodiment 1: A method for preparing an antibacterial lubricating wound dressing with anti-adhesion properties, comprising the following steps: S1. Soak the copper wire in a 10 wt.% NaOH solution to obtain a Cu(Ⅱ) solution, and then immerse the ordinary gauze in the Cu(Ⅱ) solution for 15 minutes. In an alkaline environment, the hydrogen bond network on the gauze is destroyed, causing the cellulose matrix to swell. Subsequently, the copper ions diffuse into the gaps between cellulose crystals and coordinate with the oxygen atoms of the hydroxyl groups on the cellulose chain, so that the gauze is loaded with copper ions and finally obtains the copper ion gauze Cu-IG. S2, washing the copper ion gauze Cu-IG sample obtained above with deionized water for multiple times until the pH value of the washed solution is neutral, and drying at room temperature for standby use; S3. The dried copper ion gauze Cu-IG sample was immersed in a mixed solution of polydimethylsiloxane and n-hexane, cured at 60°C for 4 h, and then immersed in dimethyl silicone oil with a viscosity of 200 mpa•s for 40 min, and finally the antibacterial lubricating wound dressing iPDMS / Cu-IG was obtained.

[0021] The polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 60:1.

[0022] Embodiment 2: The difference from Embodiment 1 is that: S1. Soak the copper wire in 10 wt.% NaOH solution to obtain Cu(Ⅱ) solution, and then immerse ordinary gauze in the Cu(Ⅱ) solution for 1 hour.

[0023] Embodiment 3: The difference from Embodiment 1 is: S1. Soak the copper wire in 10 wt.% NaOH solution to obtain Cu(Ⅱ) solution, and then immerse the ordinary gauze in the Cu(Ⅱ) solution for 2.5 h.

[0024] Embodiment 4: The difference from Embodiment 1 is that: S1. Soak the copper wire in 10 wt.% NaOH solution to obtain Cu(Ⅱ) solution, and then immerse the ordinary gauze in the Cu(Ⅱ) solution for 5.5 h.

[0025] Embodiment 5: The difference from Embodiment 1 is that: S1. Soak the copper wire in 10 wt.% NaOH solution to obtain Cu(Ⅱ) solution, and then immerse ordinary gauze in the Cu(Ⅱ) solution for 24 hours.

[0026] Embodiment 6: The difference from Embodiment 1 is: S1. Soak the copper wire in 10 wt.% NaOH solution to obtain a Cu(Ⅱ) solution, and then immerse ordinary gauze in the Cu(Ⅱ) solution for 48 hours.

[0027] Embodiment 7: A method for preparing an antibacterial lubricating wound dressing with anti-adhesion properties, comprising the following steps: S1. Soak the copper wire in 10 wt.% NaOH solution to obtain Cu(Ⅱ) solution, and then immerse the ordinary gauze in the Cu(Ⅱ) solution for 48 hours. In the alkaline environment, the hydrogen bond network on the gauze is destroyed, causing the cellulose matrix to swell. Then the copper ions diffuse into the gaps between cellulose crystals and coordinate with the oxygen atoms of the hydroxyl groups on the cellulose chain, so that the gauze is loaded with copper ions and finally the copper ion gauze Cu-IG is obtained. S2, washing the copper ion gauze Cu-IG sample obtained above with deionized water for multiple times until the pH value of the washed solution is neutral, and drying at room temperature for standby use; S3. The dried copper ion gauze Cu-IG sample was immersed in a mixed solution of polydimethylsiloxane and n-hexane, cured at 60°C for 4 h, and then immersed in dimethyl silicone oil with a viscosity of 200 mpa•s for 40 min, and finally the antibacterial lubricating wound dressing iPDMS / Cu-IG was obtained.

[0028] The polydimethylsiloxane:n-hexane (w / v) is 10%, and the mass ratio (w / w) of PDMS matrix and curing agent in polydimethylsiloxane is 60:1.

[0029] Embodiment 8: The difference from Embodiment 7 is that: S3, wherein the ratio of polydimethylsiloxane to n-hexane (w / v) is 50%.

[0030] Embodiment 9: The difference from Embodiment 7 is that: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 70%.

[0031] Embodiment 10: The difference from Embodiment 7 is: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 20:1.

[0032] Embodiment 11: The difference from Embodiment 7 is: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 30:1.

[0033] Embodiment 12: The difference from Embodiment 7 is: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 40:1.

[0034] Embodiment 13: The difference from Embodiment 7 is: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 50:1.

[0035] Embodiment 14: The difference from Embodiment 7 is: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 70:1.

[0036] Embodiment 15: The difference from embodiment 7 is: S3, wherein the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio (w / w) of the PDMS matrix and the curing agent in the polydimethylsiloxane is 80:1.

[0037] Embodiment 16: The difference from Embodiment 7 is: S3. Immerse in dimethyl silicone oil with a viscosity of 20 mpa•s for 40 min, in which the polydimethylsiloxane:n-hexane (w / v) is 33%, and the mass ratio of PDMS matrix and curing agent in polydimethylsiloxane (w / w) is 60:1.

[0038] Experimental results and analysis 1. Determination of copper ion loading on ordinary gauze In order to prove that copper ions were successfully loaded on the gauze, an X-ray photoelectron spectroscopy test was performed on the Cu-IG sample gauze in Example 6. The experimental process is as follows: X-ray photoelectron spectroscopy (XPS) was used to perform full spectrum width scanning and narrow scanning on the Cu-IG surface to analyze the chemical state of the elements.

[0039] The results are as follows Figure 2 As shown, a Cu 2p 3 / 2 peak, indicating the successful loading of copper in the sample gauze.

[0040] 2. Determination of the effect of ordinary gauze soaking time in Cu(Ⅱ) solution on the content of loaded copper ions In order to explore the relationship between the loading amount of copper ions on ordinary gauze and time, ICP-OES test was performed on the Cu-IG sample gauze in Examples 1 to 6. The specific experimental process is as follows: ICP-OES inductively coupled plasma was used to test the gauze soaked in the solution for different time periods to analyze the loading amount of copper ions.

[0041] The results are as follows Figure 3 As shown in the figure, the change in the amount of copper ion loading on the ordinary gauze was small after 12 hours, indicating that it was fully loaded in about 12 hours.

[0042] 3. Determination of the effect of n-hexane content on the pore size of Cu-IG n-Hexane can adjust the viscosity of PDMS. In order to explore the effect of n-hexane content on the pore size of Cu-IG, scanning electron microscopy analysis was performed on the iPDMS / Cu-IG sample gauze in Examples 6 to 9. The experimental process is as follows: the gauze is glued to the sample stage with conductive glue, its surface is sprayed with gold for 50 s, and the appearance morphology is observed using a scanning electron microscope at an accelerating voltage of 10 kV.

[0043] The results are as follows Figure 4 As shown in the figure, with the decrease of n-hexane content, the pore blockage of Cu-IG by PDMS gradually increases. When the mixed solution of polydimethylsiloxane and n-hexane is 33% (w / v) and (PDMS)-curing agent (w / w=60:1), there is an appropriate amount of PDMS on the gauze fiber, so this ratio is selected to prepare the sample gauze.

[0044] 4. Determination of adhesion of samples prepared with different ratios of PDMS and curing agent (w / w) Different ratios of PDMS curing agent will directly affect the adhesion of the sample. Therefore, in order to find the best ratio, the iPDMS / Cu-IG sample gauze in Examples 6 and 10 to 15 was used to simulate the adhesion to the wound when peeled under wound bleeding conditions. The experimental process is as follows: 20 μL of blood was dripped between two pieces of gauze. After the blood dried, the adhesion of the sample was measured using a universal testing machine at a tensile speed of 20 mm / min. Ordinary gauze and commercially available low-adhesion dressings were used as controls.

[0045] The results are as follows Figure 5 As shown, the adhesion of the sample gauze is less than that of ordinary gauze, and when the PDMS curing agent ratio is less than 70:1, the adhesion of the gauze is smaller than that of the commercially available vaseline gauze, that is, it has better anti-secondary injury performance.

[0046] 5. Softness and hardness determination of samples prepared with different ratios of PDMS and curing agent (w / w) Different proportions of PDMS curing agent will directly affect the hardness of the sample, and the hardness of the dressing will further affect the comfort of the patient. Therefore, in order to obtain a dressing with appropriate hardness, the iPDMS / Cu-IG sample gauze in Examples 6 and 10 to 15 was subjected to compression force testing. The experimental process is as follows: the gauze was cut into a size of 4 cm × 2 cm, and the hardness of the sample was measured at a speed of 10 mm / min using a universal testing machine. Three parallel experiments were performed.

[0047] The results are as follows Figure 6 As shown in the figure, when the ratio of PDMS to curing agent is greater than 60:1, the softness of the sample gauze is similar to that of ordinary gauze. Figure 5 and Figure 6 As a result, we selected PDMS and curing agent with a ratio of 60:1 (w / w) as the standard for sample preparation.

[0048] 6. Determination of the adaptability of dimethyl silicone oil with different viscosities to sample gauze The viscosity of dimethyl silicone oil will affect the adaptability of the sample gauze. Therefore, in order to obtain a sample gauze with good adaptability, the iPDMS / Cu-IG sample gauze in Example 6 and Example 16 was characterized for its adaptability. The specific experimental process is as follows: the cured gauze is immersed in dimethyl silicone oil of different viscosities, taken out and placed on the finger joints, and when the fingers are moving, it is observed whether it fits the finger joints.

[0049] The results are as follows Figure 7 As shown in the figure, the sample gauze soaked in dimethyl silicone oil with a viscosity of 200 mpa•s can bend freely along the finger joints and has good adaptability.

[0050] 7. Determination of antifouling performance In order to verify that the sample gauze can prevent external pollutants from penetrating the dressing, bacteria are used as representatives of pollutants to perform an anti-fouling test on the iPDMS / Cu-IG sample gauze in Example 6. The experimental process is as follows: First, the fluorescent Escherichia coli MG1655-hslu-mneongreen is cultured, that is, 5mL LB broth medium is added to the shaking tube, and fluorescent bacteria are added, and cultured overnight in a 37°C constant temperature shaker. Then use a glass slide as a substrate, cover the gauze on top, and drop an appropriate amount of fluorescent bacteria on the tilted gauze. Observe the glass substrate under a microscope to see if there are fluorescent bacteria to judge the anti-fouling condition of the gauze.

[0051] The results are as follows Figure 8 As shown, only a small amount of fluorescent bacteria can be observed on the glass substrate covered by the sample gauze, while a large amount of fluorescent bacteria can be observed on the ordinary gauze, proving that the iPDMS / Cu-IG gauze has a good anti-fouling effect.

[0052] 8. Determination of moisturizing properties In order to verify that iPDMS / Cu-IG has moisturizing properties, ordinary gauze and vaseline gauze were used as control groups to test the moisturizing ability of the iPDMS / Cu-IG sample gauze of Example 6. The experimental process is as follows: Pork was cut into cubes of 2cm×2cm×1cm and the outer layer was wrapped with gauze. Ordinary gauze and commercially available vaseline gauze were used as controls, and the weight of pork (together with gauze) was weighed regularly. The initial mass and the mass of the samples at different time periods were recorded, and the water loss rate was calculated.

[0053] The results are as follows Fig. 9 As shown, the sample gauze has the lowest water loss rate, showing better moisturizing effect than vaseline gauze.

[0054] 9. Water vapor transmission rate measurement The water vapor transmission rate (WVTR) of gauze was determined according to the American Society for Testing and Materials (ASTM) standard. The specific steps are as follows: 10 mL of deionized water was placed in a bottle with a diameter of 12.5 mm, and then the gauze was cut into 2 cm × 2 cm sizes, the gap between the gauze and the bottle mouth was sealed and weighed. The sample bottle was then placed in a constant temperature and humidity incubator (temperature 37°C, relative humidity 30±5%). The total mass of the bottle (together with the gauze) was measured regularly, and the water vapor transmission rate was calculated.

[0055] The results are as follows Fig.10 As shown, the water vapor permeability of iPDMS / Cu-IG is close to that of ordinary gauze, indicating that gas exchange can be achieved.

[0056] 10. Determination of antibacterial ability In order to verify the antibacterial ability of iPDMS / Cu-IG, ordinary gauze was used as a control, and the iPDMS / Cu-IG sample gauze in Example 6 was used to test the antibacterial performance of Escherichia coli and Staphylococcus aureus. The experimental process is as follows: the sample was cut into a size of 30 mm × 30 mm, placed in a clean bench and sterilized by ultraviolet irradiation for 30 min. Then the sample and bacteria were placed in a constant temperature shaker at 37 ° C for 24 h and then plated. That is, 90 μL PBS buffer solution was added to each well of a 96-well plate, followed by 10 μL bacterial solution, and a 10-fold gradient dilution was performed. Then 20 μL of gradient diluted bacteria were taken from each well for plated (three times in parallel). Finally, the agar plate was inverted and placed in a constant temperature and humidity incubator at 37 ° C overnight. The plate was imaged and the number of colonies was manually counted to evaluate the antibacterial performance of the gauze.

[0057] The results are as follows Fig.11As shown, for Escherichia coli and Staphylococcus aureus, the antibacterial effects of iPDMS / Cu-IG and ordinary gauze differed by about 3 orders of magnitude, indicating that the gauze has good antibacterial ability.

[0058] 11. Cytotoxicity assay In order to verify that iPDMS / Cu-IG does not affect cell activity, ordinary gauze, vaseline gauze, and Atrauman® Ag were used as controls and the iPDMS / Cu-IG sample gauze of Example 6 was used to perform cytotoxicity analysis on L929 cells. The experimental process is as follows: cells were cultured in DMEM containing 10% FBS, and the cell compatibility was detected by CCK-8 method. First, 100 μl (10 4 cells), and placed them in a CO2 cell culture incubator for 24 h to allow the cells to grow on the 96-well plate. The tested samples were cut into 1 cm × 1 cm size and extracted with culture medium for 24 h. The cells that did not receive any treatment and the wells containing culture medium were used as negative controls and blank controls, respectively. Then, the culture medium was replaced with 100 μL of gauze extract in each well, and 10 μL of CCK-8 was added to each well after 48 h of culture, and cultured in the incubator for 1 h. Finally, the absorbance of the cells at 450 nm was measured using an enzyme reader, and the cell survival rate was calculated.

[0059] The results are as follows Fig.12 As shown in the figure, the survival rate of cells in the sample gauze group is above 95%, which is not much different from cells cultured normally without any interference factors, ordinary gauze and commercially available medical dressings. According to the relevant standards of GB / T 1688.6.5-2003 / ISO10993-5, when the survival rate is lower than 70%, it is considered to be potentially toxic. Therefore, it can be considered that the iPDMS / Cu-IG prepared in this experiment is not toxic.

[0060] 12. Determination of wound healing ability In order to verify that iPDMS / Cu-IG can promote wound healing, burn wounds were established on the backs of SD rats. Ordinary gauze and Atrauman® Ag were used as control groups, and the iPDMS / Cu-IG sample gauze of Example 6 was used to monitor the healing process of burn wounds in SD rats to evaluate the healing ability. The specific experimental process is as follows: 6 to 8 week old SD rats (150g to 180g) were selected as burn wound models. First, the rats were anesthetized with 2% sodium pentobarbital, and the backs of male rats were depilated with a shaver and depilatory cream, and then the skin on the backs of the rats was repeatedly cleaned with alcohol cotton pads and disinfected. The custom-made metal soldering iron (φ=8mm) that had been sterilized by high pressure was heated to 150°C and pressed on the back of the rat with uniform force for 10 s. A second-degree circular burn wound (average area = 50mm) was created on the back of each rat.2 ). After the wound was established, it was disinfected with 75% alcohol for 10 s. Then, different groups of gauze with a size of 2 cm × 2 cm were placed on the wound, bandaged and fixed with 3M wound dressing, and the gauze was changed on the 1st, 4th, 7th, and 11th days.

[0061] The results are as follows Fig.13 As shown in the figure, the wound began to change after 4 days of treatment. Obvious healing was observed on the 11th day, and the iPDMS / Cu-IG group showed relatively good wound closure effects at different time points compared with the plain gauze and Atrauman@Ag gauze groups, and was close to complete closure on the 14th day.

[0062] 13. Histopathological analysis To further verify the reason why iPDMS / Cu-IG can promote wound healing, histopathological analysis was performed. The experimental process was as follows: Rats were killed on the 7th and 14th days, respectively. Skin wound tissues were collected, fixed with 4% paraformaldehyde solution, and embedded in paraffin to prepare 3 to 5 μm thick pathological sections. After hematoxylin and eosin (H&E) and Masson's trichrome staining (Masson), histological images were observed under an optical microscope. Granulation tissue thickness and collagen deposition were analyzed using Image-J software.

[0063] like Fig.14 As shown in a, on the 7th day, all groups showed inflammation, among which the ordinary gauze group was more serious, and the defect of the dermis was also more serious; while the Atrauman@Ag group and the iPDMS / Cu-IG group had partial defects in the dermis, and the epidermis of the iPDMS / Cu-IG group had begun to form. On the 14th day, the iPDMS / Cu-IG group showed a relatively better anti-inflammatory effect and better dermal regeneration. The growth of granulation tissue was further observed, as shown in Fig.14 As shown in b, compared with other groups, the granulation tissue in the iPDMS / Cu-IG group was thicker and had better growth.

[0064] like Fig.15 As shown. The formation of collagen deposition can be observed in all groups after Masson staining. The expression of collagen in the ordinary gauze group was low, and the wound healing was slow. The iPDMS / Cu-IG group showed a higher expression of collagen, and obvious skin appendages such as hair follicles and blood vessels were observed. These results show that the iPDMS / Cu-IG group can promote the formation of wound collagen deposition and effectively promote the healing of burn wounds.

[0065] The iPDMS / Cu-IG prepared in the present invention reduces adhesion to the wound due to the wrapping of gauze fibers by PDMS, avoiding secondary damage to the wound when changing the dressing, and its excellent lubricity ensures that the sample has good antifouling properties; in addition, copper ions show excellent antibacterial effects on Escherichia coli and Staphylococcus aureus, thus giving iPDMS / Cu-IG good bactericidal ability. It is worth noting that the preparation method of iPDMS / Cu-IG is simple, the production cost is low, and it is conducive to large-scale preparation and production.

[0066] The above description is only used to illustrate the technical solution of the present invention rather than to limit it. Other modifications or equivalent substitutions made to the technical solution of the present invention by ordinary technicians in this field should be included in the scope of the claims of the present invention as long as they do not depart from the spirit and scope of the technical solution of the present invention.

Claims

1. A method for preparing an antibacterial lubricating wound dressing with anti-adhesion properties, characterized in that: The following steps are involved: S1. Soak the copper wire in a 10 wt.% NaOH solution to obtain a Cu(Ⅱ) solution, and then immerse the ordinary gauze in the Cu(Ⅱ) solution. In an alkaline environment, the hydrogen bond network on the gauze is destroyed, causing the cellulose matrix to swell. Subsequently, the copper ions diffuse into the gaps between the cellulose crystals and coordinate with the oxygen atoms of the hydroxyl groups on the cellulose chain, so that the gauze is loaded with copper ions and finally obtains the copper ion gauze Cu-IG. S2, washing the copper ion gauze Cu-IG sample obtained above with deionized water for multiple times until the pH value of the washed solution is neutral, and drying at room temperature for standby use; S3. The dried copper ion gauze Cu-IG sample is immersed in a mixed solution of polydimethylsiloxane and n-hexane for solidification, and then immersed in dimethyl silicone oil again to finally obtain the antibacterial lubricating wound dressing iPDMS / Cu-IG.

2. The preparation method according to claim 1, characterized in that: In step S1, the time for the copper ion loading of ordinary gauze to reach stability is 15 minutes to 48 hours.

3. The preparation method according to claim 1, characterized in that: In the step S3, the ratio of polydimethylsiloxane to n-hexane (w / v) is 10% to 70%.

4. The preparation method according to claim 1, characterized in that: In the step S3, polydimethylsiloxane is formed by thermally polymerizing a PDMS matrix and a curing agent in a certain proportion, wherein the mass ratio (w / w) of the PDMS matrix and the curing agent is 20-80:

1.

5. The preparation method according to claim 1, characterized in that: In step S3, the viscosity of the dimethyl silicone oil is 20 mPa•s or 200 mPa•s, and the immersion time in the dimethyl silicone oil is 40 min.

6. An antibacterial lubricating wound dressing with anti-adhesion properties is prepared according to the preparation method according to any one of claims 1 to 5.

7. Use of the antibacterial lubricating wound dressing with anti-adhesion function according to claim 6 in the antibacterial field of medical materials.

Citation Information

Cited By

  • Degradable medical gauze based on plant fibers and production process thereof

    CN121059870A